Working with the institutional review board - Byerly, Wesley G. (American journal of health-system pharmacy, 2009)
Working with an institutional review board (IRB) to ensure compliance and ethical conduct of research involving human subjects is discussed. The Department of Health and Human Services (DHHS) and Food and Drug Administration regulations for the conduct of human research are grounded in the principles of the Belmont Report. By establishing the requirements for the function and operation of the IRB, the criteria needed for the review and approval of research, and the requirements for obtaining and documenting informed consent, the federal regulations help ensure the safety, rights and welfare of subjects. In developing research protocols and submissions to the IRB, the investigator should include clear, detailed information that addresses the regulatory requirements for the review and approval of research. Before starting a research study, review and approval by the IRB is required unless the study is determined to be minimal risk and fits one of the defined categories. Some research projects involving observation of public behavior, collection of anonymous surveys of nonvulnerable individuals in which the information is not considered sensitive, and evaluation of standard education practices may be exempt from DHHS regulations. Informed consent is central to the protection of human subjects and is required unless the IRB allows a waiver or alteration of informed consent. Once the study is approved, the investigator must conduct the study as approved by the IRB and continue to meet the regulatory requirements related to modifications, reporting unanticipated events, and continuing review. IRB review is integral to ensuring regulatory compliance and ethical conduct of research involving human subjects. Working closely with the IRB or colleagues who have had experience with the IRB will help junior investigators better understand the IRB submission and review process.